Towards nearly zero-energy residential neighbourhoods in the European Union: A case study - Nematchoua, Modeste Kameni; Marie-Reine Nishimwe, Antoinette; Reiter, Sigrid (Renewable & sustainable energy reviews, 2021)
The European Union (EU) aims to establish a guideline that requires all new buildings to comply with nearly zero-energy buildings (NZEB) by 2030. This decision involves new technologies based on concepts that meet international standards. This research aims to review the literature on ‘net zero-energy building’ and analyses the possibility of applying this research on nine statistically representative neighbourhoods of the building stock'in Belgium, depending on the built density. All the areas, grouped into four categories (urban, peri-urban, suburban, and rural neighbourhoods), were used for current energy consumption analysis and to evaluate prospective scenarios based on four major challenges, namely climate change, building renovations, photovoltaic panels, and sustainable mobility. In addition, a new approach combining several scenarios to further improve energy needs at the neighbourhood scale is also highlighted. The nine different types of neighbourhoods studied are commonly found in different countries across the EU. The average reduction in energy consumption of neighbourhoods (buildings + daily mobility) in 2040 (compared to reference year 2012) will likely reach 5.69% attributable to a 20% reduction in distances travelled, 6.48% to climate change, 12.95% to the current annual buildings renovation rate, 18.76%–100% electric cars, 22.26% for doubling the current buildings renovation rate, 31.62% and 63.25% to a light or heavy renovation of the entire building stock, respectively. Moreover, installing 20 m2 of solar panels on the rooftops of each residential building would produce renewable energy equivalent to 6.53% of the current global energy consumption. Finally, the results show that more than 90% of current energy consumption can be reduced at the neighbourhood scale (buildings + daily mobility) by combining a heavy renovation of all the buildings, electric vehicles, and photovoltaic panels. This scenario allows reaching the ‘nearly zero-energy’ target at the neighbourhood scale. •The 90% of energy consumption can be reduced by combining a heavy renovation, electric vehicles, and photovoltaic panels.•Photovoltaic panel yield is higher in rural than urban neighbourhoods.•Electric vehicles reduce up to 20% of energy consumption in neighbourhoods.